Effect of cylinder deactivation on the tribo-dynamics and acoustic emission of overlay big end bearings. (June 2014) - Mohammadpour, M; Rahmani, R; Rahnejat, H
The paper presents an integrated tribo-dynamics analysis of elliptic bore overlay big end bearings of internal combustion engines. The analysis focuses on bearing stability, frictional power loss and acoustic emission from these bearings, particularly with cylinder deactivation with larger fluctuations in engine loading. The integrated approach represents a tribo-dynamics analysis, not hitherto reported in literature, particularly under cylinder deactivation. The analysis shows that cylinder deactivation makes marginal differences in parasitic frictional losses in engine bearing performance and any significant gain would depend on the brake specific fuel consumption. It is also shown that sufficient swept volume with retained residual exhaust gas charge within the deactivated cylinders can ensure bearing whirl stability. Partially deactivated engine configurations exhibit a lower average steady noise emission, but with a higher degree of transient content. This suggests that there would be a greater contribution to engine rumble with deactivated cylinders.